Branding en el posicionamiento de la picantería El Manaba en la ciudad de Guayaquil - Guacho Cerezeda, Joseline Jurneth (2023)
The investigation focuses on the "El Manaba" picantería, located in the city of Guayaquil. With a history of 12 years, this restaurant has two locations in Bastión Popular. The business stands out for being a restaurant that offers services of seafood dishes, little positioning and brand recognition within the market has been shown, affecting its income. Among the unfavorable factors are the lack of presence in digital media and insufficient investment in the business. To address this problem, it has been decided to implement branding strategies. These strategies are based on research from previous studies related to the field. In the field of research, a mixed approach was used, using tools such as surveys and interviews in order to understand the tastes and preferences of customers as well as their influence on brands.